Applicability of agent based systems in customer knowledge management - Homayouni, Seyed Mahdi; Tang, Sai Hong (Universiti Utara Malaysia, 2008)
Customers were introduced as one of the brilliant resources of knowledge for the companies and enterprises. This paper proposes to integrate the agent-mediated knowledge management and the customer knowledge management systems. This is to provide a framework to acquire the cryptic knowledge from and related to the customers and provides required knowledge for them. The abilities of agents in knowledge management systems are reviewed in advance then these capabilities are collated to the requirements of the customer knowledge management. A simple model for agent-mediated customer knowledge management systems is proposed as the final goal of this paper.